A powder metallurgy method for manufacturing Ti-6Al-4V with wrought-like microstructures and mechanical properties via hydrogen sintering and phase transformation (HSPT). (October 2015) - Paramore, James D.; Fang, Z. Zak; Sun, Pei; Koopman, Mark; Chandran, K.S. Ravi; Dunstan, Matt
Graphical abstract: Abstract: In this paper, the feasibility of producing Ti-6Al-4V with a range of wrought-like microstructures and mechanical properties via a novel powder metallurgy (PM) process with simple heat treatments is investigated. The wrought-like PM Ti-6Al-4V is obtained by sintering blended elemental (BE) powder in a hydrogen atmosphere, followed by conventional Ti-6Al-4V heat treating profiles. This is achieved without resorting to energy-intensive thermomechanical processing (TMP) that is compulsory for producing high performance titanium alloys via wrought processing or traditional powder metallurgy.